A case of contralateral inguinal lymph node metastases from breast cancer - Kimoto, Takeo (Surg Case Rep, 2021)
BACKGROUND: Breast cancer is well known to tends to invade through the lymphatic chains mainly to the axillary and subclavian nodes or occasionally to the internal mammary nodes. However, inguinal lymph node metastasis from breast cancer is extremely rare. CASE PRESENTATION: We have experienced a case of an 82-year-old woman showing left inguinal lymph node metastases from right breast cancer. Previously, she had received five times abdominal operations and left artificial bone head replacement for metamorphous hip-joint disease. Although the metastases were firstly detected 46 months after the breast surgery, they had already existed at the time of the breast operation, which was retrospectively re-evaluated by CT examination. The progression pattern of inguinal lymph node metastases had much correlated with that of the breast cancer. She underwent inguinal lymph node dissections. Pathological findings revealed them being compatible with breast cancer origin. CONCLUSIONS: This is the sixth case having been reported in English literature. Besides, this is the first case showing the contralateral spread to the primary breast cancer. One of the causes of this complex metastatic pattern is thought be ascribed to the previously performed prolific abdominal operations.